2019
DOI: 10.1007/s10562-019-02856-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Analysis of Guaiacol Hydrodeoxygenation

Abstract: Kinetics of guaiacol hydrodeoxygenation (HDO) was studied using supported Mo x C-SBA-15 and as a comparison 5 wt% Pt/C under 30 bar hydrogen at 200°C and 300°C. Catalyst characterization was done by a range of physical methods including also determination of the amount of coke and the nature of adsorbed species. Pt/C gave 2-methoxycyclohexanol as the main product, whereas Mo 2 C-SBA-15 promoted direct deoxygenation exhibiting also strong adsorption of guaiacol on the catalyst surface and formation of oligomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 38 publications
0
12
0
3
Order By: Relevance
“…Only 3% of ( 4) was seen at 3 h and none was detected at 6 h. This indicates that ( 4) is an intermediate in the production of (1). It has been reported that the hydrogenolysis of the methyl-oxygen bond (demethylation) of the methoxy group of GUA to form catechol is the first stage of the reaction, followed by a second stage leading to the elimination of one of the hydroxyl groups (deoxygenation) to produce phenol [12,63,64]. Over the BCR catalyst, phenol was also produced via the direct demethoxylation of GUA.…”
Section: Catalytic Hdo Of Guamentioning
confidence: 99%
“…Only 3% of ( 4) was seen at 3 h and none was detected at 6 h. This indicates that ( 4) is an intermediate in the production of (1). It has been reported that the hydrogenolysis of the methyl-oxygen bond (demethylation) of the methoxy group of GUA to form catechol is the first stage of the reaction, followed by a second stage leading to the elimination of one of the hydroxyl groups (deoxygenation) to produce phenol [12,63,64]. Over the BCR catalyst, phenol was also produced via the direct demethoxylation of GUA.…”
Section: Catalytic Hdo Of Guamentioning
confidence: 99%
“…In work, Mo 2 C/SBA‐15 catalyst has been prepared using hexamethylenetetramine ammonium heptamolybdate complex as a precursor. Kinetics of guaiacol hydrodeoxygenation was studied using supported Mo 2 C/SBA‐15 under 30 bar hydrogen at 200 °C and 300 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Aún hace falta información acerca del estudio termodinámico (∆ ,∆ ,Keq), Sulman et al [69] estimaron entalpías y la energía libre de Gibbs de las rutas de reacción involucradas en la HDO de guayacol (Figura 4.9), a partir de una base de datos ChemCAD v.5.0 a condiciones estándar y a temperaturas entre 200 y 300 °C, 25 bar. La Figura 4.9 muestra las vías de reacción global para la HDO de guayacol mientras que los compuestos encerrados en circulo son moléculas representativas visto en la HDO de anisol.…”
Section: Efecto De La Temperatura En La Hdo Anisolunclassified